Climatic vulnerabilities and ecological preferences of soil invertebrates across biomes. Issue 4 (3rd December 2019) - Bastida, Felipe; Eldridge, David J.; Abades, Sebastián; Alfaro, Fernando D.; Gallardo, Antonio; García‐Velázquez, Laura; García, Carlos; Hart, Stephen C.; Pérez, Cecilia A.; Santos, Fernanda; Trivedi, Pankaj; Williams, Mark A.; et al.
Abstract: Unlike plants and vertebrates, the ecological preferences, and potential vulnerabilities of soil invertebrates to environmental change, remain poorly understood in terrestrial ecosystems globally. We conducted a cross‐biome survey including 83 locations across six continents to advance our understanding of the ecological preferences and vulnerabilities of the diversity of dominant and functionally important soil invertebrate taxa, including nematodes, arachnids and rotifers. The diversity of invertebrates was analyzed through amplicon sequencing. Vegetation and climate drove the diversity and dominant taxa of soil invertebrates. Our results suggest that declines in forest cover and plant diversity, and reductions in plant production associated with increases in aridity, can result in reductions of the diversity of soil invertebrates in a drier and more managed world. We further developed global atlases of the diversity of these important soil invertebrates, which were cross‐validated using an independent database. Our study advances the current knowledge of the ecological preferences and vulnerabilities of the diversity and presence of functionally important soil invertebrates in soils from across the globe. This information is fundamental for improving and prioritizing conservation efforts of soil genetic resources and management policies. Abstract : see also the Perspective by Phillips et al